PENGARUH KEPERCAYAAN TERHADAP KOMITMEN NASABAH PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. PADA UNIT CITRA SUDIANG MAKASSAR - Yustika Nur; Fadlina Fadlina; Busrin Raihan Masúd (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
This research aims to investigate the influence of trust on consumer commitment in a specific context. Data collection was conducted through questionnaire surveys, and data analysis was performed using linear regression method in SPSS software version 22. The initial analysis results indicate a significant positive relationship between the level of trust and consumer commitment. Furthermore, the findings suggest that high levels of trust tend to have a positive impact on high levels of consumer commitment. This confirms that trust plays an important role in shaping consumer commitment. The analysis also reveals that trust has a substantial influence on consumer commitment. More specifically, high levels of trust are associated with high levels of consumer commitment. These findings indicate that the higher the level of trust consumers have in a product, service, or brand, the stronger their commitment to it. Overall, this research provides a deeper understanding of the role of trust in shaping consumer commitment. The implications of these findings can be used as a basis for marketing practitioners to enhance their strategies in building strong consumer trust, which in turn can increase consumer commitment to the products, services, or brands offered.